Clinical spectrum and pleiotropic nature of CDH1 germline mutations. Issue 4 (19th January 2019) - Figueiredo, Joana; Melo, Soraia; Carneiro, Patrícia; Moreira, Ana Margarida; Fernandes, Maria Sofia; Ribeiro, Ana Sofia; Guilford, Parry; Paredes, Joana; Seruca, Raquel
Abstract : CDH1 encodes E-cadherin, a key protein in adherens junctions. Given that E-cadherin is involved in major cellular processes such as embryogenesis and maintenance of tissue architecture, it is no surprise that deleterious effects arise from its loss of function. E-cadherin is recognised as a tumour suppressor gene, and it is well established that CDH1 genetic alterations cause diffuse gastric cancer and lobular breast cancer—the foremost manifestations of the hereditary diffuse gastric cancer syndrome. However, in the last decade, evidence has emerged demonstrating that CDH1 mutations can be associated with lobular breast cancer and/or several congenital abnormalities, without any personal or family history of diffuse gastric cancer. To date, no genotype–phenotype correlations have been observed. Remarkably, there are reports of mutations affecting the same nucleotide but inducing distinct clinical outcomes. In this review, we bring together a comprehensive analysis of CDH1 -associated disorders and germline alterations found in each trait, providing important insights into the biological mechanisms underlying E-cadherin's pleiotropic effects. Ultimately, this knowledge will impact genetic counselling and will be relevant to the assessment of risk of cancer development or congenital malformations in CDH1 mutation carriers.